Fight Alone or Together? The Need to Belong - Changxia Ke (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
Alliances often face both free-riding and hold-up problems, which under- mine the effectiveness of alliances in mobilizing joint fighting effort. Despite of these disadvantages, alliances are still ubiquitous in all types of contests. This paper asks if there are non-monetary incentives to form alliances, e.g., intimidating/discouraging the single player(s) who is/are left alone. For this purpose, I compare symmetric (2 vs. 2) and asymmetric (2 vs. 1) contests to their equivalent 4-player and 3-player individual contests, respectively. We find that alliance players in symmetric (2 vs. 2) contests behave the same as those in equivalent 4-player individual contests. However, in asymmetric (2 vs. 1) contests, stand-alone players were strongly discouraged to exert effort (especially the females), compared to the 3-player individual contests. Alliance players may have anticipated this effect and also reduced their effort, if alliances share the prize according to the merit rule. Behavioural factors such as the need to belong can help reconcile the paradox of alliance formation.
urn:nbn:de:bvb:19-epub-17247-2
Keywords: D72; D74; C91; 330; Alliance Formation; Contest and Conflict; Experiment